A latent trajectory analysis of young sexual and gender minorities' adherence to three rectal microbicide placebo formulations (MTN-035; a randomized crossover trial) - Seul Ki Choi; José Bauermeister; Ryan C. Tingler; Sherri Johnson; Nicole Macagna; Ken Ho; Craig Hoesley; Albert Liu; Noel Kayange; Thesla Palanee-Phillips; Suwat Chariyalertsak; Pedro Gonzales; et al. (BMC, 2023)
Abstract Background Rectal microbicides (RM) are biomedical HIV prevention products that aim to prevent or reduce the transmission of HIV and other sexually transmitted infections (STIs). RM modalities may be beneficial for populations who have complex lifestyles, difficulties adhering to pre-exposure prophylaxis (PrEP) regimens, and/or have limited access to care. MTN-035 (DESIRE; Developing and Evaluating Short-Acting Innovations for Rectal Use), a randomized crossover trial, aimed to evaluate the safety and acceptability of, and adherence to, three placebo RM modalities (douche, insert, and suppository) prior to receptive anal intercourse. Methods We conducted latent trajectory analysis to identify clusters of individuals who shared similar trajectories in acceptability and adherence for each product (douche, insert, and suppository) over time. We analyzed weekly short messaging service (SMS) use reports for each modality as reported by enrolled sexual and gender minority (SGM) participants. Results Two trajectories for each product were identified: a "protocol compliant" trajectory (i.e., at least one product use occasion per week) and "high use" trajectory (i.e., more than three product use occasions per week). Participants with high use were more likely to lack access to PrEP and have higher intentions to utilize RM modalities compared to those who were protocol compliant. Conclusions This study highlighted high adherence to RM modalities among SGM. As research into viable HIV prevention modalities continues to evolve, tailored intervention strategies are needed to support the uptake of and adherence to alternative prevention modalities that are behaviorally congruent with targeted users. Trial registration NCT03671239 (14/09/2018).